The Effect of Dispersion on the Informativeness of Consensus Analyst Target Prices - Palley, Asa B.; Steffen, Thomas D.; Zhang, X. Frank (Management Science, 2025)
Consensus analyst target prices are widely available online at no cost to investors. In this paper, we examine how the amount of dispersion in the individual target prices comprising the consensus affects the predictive association between the consensus target price and future returns. We find that returns implied by consensus target prices and realized future returns are positively correlated when dispersion is low, but they become highly negatively correlated when dispersion is high. Further analyses suggest that the differing effect of dispersion stems from incentive-driven staleness in price targets by some analysts after bad news. As a stock performs poorly and some analysts are slow to update their target prices, dispersion increases, and the consensus target price becomes too high. This has important implications for how consensus analyst target prices should inform investment decisions. We show that a hedge strategy taking a long (short) position in stocks with the highest predicted returns among stocks with the lowest (highest) dispersion earns more than 11% annually. Finally, we show that the negative correlation between consensus-based predicted returns and future realized returns for high-dispersion stocks exists mainly for stocks with high retail interest, suggesting that unsophisticated investors are misled by inflated target prices that are available freely online. This paper was accepted by Suraj Srinivasan, accounting. Funding: The authors acknowledge financial support from Indiana University and Yale University. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2021.03549 .